The Civilian Conservation Corps in Colorado, 1933-1942 : volume 1, U.S. Forest Service and Bureau of Indian Affairs camps - Audretsch, Robert W. (Indianapolis, IN : Dog Ear Publishing, 2017)
"The world was without hope for many of Colorado's young men in 1933. Youth unemployment was 25 percent and another 29 percent were working only part-time. Many quit school before graduation to work odd jobs to support their families. Others took to hitching rides on railroad cars desperate for a new opportunity. Even young men who finished their schooling were without work as they had no job experience or training. Then, in 1933, with the beginning of the Civilian Conservation Corps (CCC) young men could go to work in Colorado's national parks, state parks, national forests and other public lands. They no longer worried where their next meal would come from. Now they could learn new job skills. In Colorado, CCC boys planted trees, erected fences and telephone lines, and put out forest fires. Today we still use the roads and trails they built. CCC work was made to last. At the program's end in 1942, over 30,000 Colorado men served at over one hundred twenty camps. And work was completed in nearly every county in the state."--Back cover.
Includes bibliographical references (pages 205-207) and index.
Keywords: Civilian Conservation Corps (U.S.) -- History; Civilian Conservation Corps (U.S.) -- Registers; Civilian Conservation Corps (U.S.) -- Indexes; Public service employment -- Colorado -- History; Conservation of natural resources -- Colorado -- History; Forest conservation -- Colorado -- History